AS03-adjuvanted H5N1 vaccine enhances immune response by modulating NR4A1, SDC1, ID3 genes, and reducing cortisol - Lairun Jin; Jingxin Li; Fengcai Zhu (Taylor & Francis Group, 2024)
The AS03-adjuvanted H5N1 influenza vaccine induces significantly higher immune responses compared to the non-adjuvanted H5N1 vaccine. However, the immunological mechanisms underlying this enhancement remain unclear. We aimed to identify the key genes and pathways involved in the immune response to the AS03-adjuvanted H5N1 vaccine compared to the non-adjuvanted H5N1 vaccine. The expression profiles of GSE102012 and GSE112293 were downloaded from the Gene Expression Omnibus database to identify differentially expressed genes between AS03-adjuvanted and non-adjuvanted H5N1 vaccine groups. Subsequently, the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed using the Database for Annotation, Visualization, and Integrated Discovery online tool. The protein-protein interaction (PPI) networks were constructed by the Search Tool for the Retrieval of Interacting Genes database. Through cluster analysis of the PPI network, three hub genes, namely NR4A1, SDC1, and ID3, were identified as pivotal players in the intricate network of interactions. The ID3 was up-regulated, and the other two hub genes were down-regulated. The results of the GO analysis highlighted enrichment in seven biological processes, three cellular components, and two molecular functions among the differentially expressed genes. The KEGG pathway analysis revealed the involvement of the Cushing syndrome pathway. The AS03-adjuvanted H5N1 vaccine may enhance immune responses through suppressing the NR4A1 gene and the SDC1 gene, upregulating the ID3 gene, and reducing cortisol production compared to the non-adjuvanted H5N1 vaccine.